Dehalogenase-Producing Alkaliphilic Bacteria and their Bioremediation Potential - Wahhab, Batool Hazim Abdul; Huyop , Fahrul; Wahab , Roswanira Abdul; Al-Nimer , Marwan Salih (American Journal of Biology and Natural Sciences, 2025)
Pollutants, especially halogenated ones, pose a serious threat to humans, animals, and plants because most are pervasive in the environment due to their resistance to degradation by microorganisms or through exposure to environmental elements. One sustainable way to remove this group of pollutants from the environment is through bioremediation assisted by suitable microorganisms, as fungi and bacteria. Bioremediation using bacteria as dehalogenase-producing alkaliphilic bacteria has been shown useful in remediating organohalogen-based pollutants. Most alkaliphilic bacteria have been isolated from harsh ecosystems such as soda lakes, characterized by high pH and occasionally high salinity, the first resulted from excess sodium compared to calcium in basaltic rocks, forming carbonate-rich, alkaline aquatic habitats. Bioprospecting works, isolating dehalogenase-producing alkaliphilic bacteria from soda lakes, has successfully yielded halogen-degrading enzymes, which successfully nullify the toxicity of the compounds. In this review, we describe microorganisms in soda lakes; and the distribution of alkaliphiles in these soda lakes along with the utility of alkaliphiles in bioremediation. Bioremediation of polluted alkaline water habitats has emerged as the most pressing issue of biotechnological relevance nowadays.